Simplified nonlinear model for the weight estimation of FPSO plant topside using the statistical method. (17th August 2016) - Ha, Sol; Seo, Seong-Ho; Roh, Myung-Il; Shin, Hyunkyoung
Abstract : The weight information of an FPSO plant, especially of the FPSO (floating, production, storage, and off-loading), is one of the important data needed to estimate the amount of production material (e.g. plates) and to determine the suitable production method for its construction. In addition, the weight information is a key factor that affects the building cost and the production period of the FPSO plant. Although the importance of the weight has long been recognised, the weight, especially of the topside, has been roughly estimated using the existing design and production data as well as the designer's experience. To improve this task, a nonlinear simplified model for the weight estimation of the FPSO plant topside using the statistical method was developed in this study. To do this, various past records on the estimation of the weight of the FPSO plant were collected through literature survey, and then correlation analysis and multiple regression analysis were performed to develop a nonlinear simplified model for weight estimation. Finally, to evaluate the applicability of the developed model, it was applied to an example of the weight estimation of the FPSO plant topside. The results showed that the developed model can be applied to the weight estimation process of the FPSO plant at the early design stage.